A computational exploration of a possible alternative to nucleotides as the basis of a genetic alphabet - Ní Chaoimh, Lavina Dewdney (Trinity College (Dublin, Ireland). School of Chemistry, 2012)
One of the most fundamental questions in molecular biology is why nature has chosen Adenine (A), Cytosine (C), Guanine (G), Uracil (U)/Thymine (T) for the genetic alphabet. Although much is known about the structure and composition of DNA the reason behind nature's particular choice of nucleotide alphabet over the many conceivable alternatives is not self-evident. Most studies have pursued physicochemical aspects of the problem while informatics aspects have been largely neglected, although they have been recently shown to play a fundamental role.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.